Code Switching Analysis in Gita Savitri’s YouTube Channel: A Sociolinguistic Study - Abd Halim; Nur Mutmainna Halim; Dahniar Dahniar; Rukmini Mahmud (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2022)
Our country, Indonesia, is the home of bi/multi-lingual speakers where most people are able to speak two languages at least or more. Most speakers are even good at foreign language, English in particular. Thus, this background causes code switching happens noticeably commonplace. Since it happens very frequently, for some cases it becomes habit. This phenomena also occurs to Gita Savitri, an Indonesian YouTuber who is able to speak several languages. This research aims: 1) to identify types of code switching, and 2) to describe some reasons of the used of code switching by Gita Savitri in selected videos in her YouTube channel. Those videos were chosen based on the sequence and context of speech that is dominant in the occurrence of code switching. This study employs qualitative descriptive method. The data in this research was Gita’s utterances. Researchers used the theory proposed by Hoffman (1991) to analyse the data. Results of this study found fifty times of code-switching occurrence. There were twenty-one utterances of intra-sentential code switching; twenty utterances of inter-sentential code switching; and nine utterances of emblematic code switching. Also, some reasons by Gita Savitri made code switching in her videos were: seven utterances talking about certain topics, five utterances quoting other people, four utterances affirming something or expressing solidarity, four utterances included in connecting sentences, four utterances adventure used for clarification, one speaker’s utterance used to clarify the conversation content to the opposite. Also, five utterances used by speaker’s to express the identity of a group. At last, it is hoped that the findings of this research could be a novel contribution in a field of sociolinguistics, also a new insight for code-switching phenomenon which is probably found very common nowadays in Indonesia.